Global Value Chain: Islamic Economics and Finance Position - Laila Masruro Pimada (Universitas Islam Negeri Raden Mas Said Surakarta, 2021)
The growing number of Muslim populations promotes significant development on Islamic economic and finance activities called halal industry. While the halal industry is experiencing positive growth in the last four years, the Global Value Chain (GVC) – the chain of system that drives international trades and global economic activities – remains stagnant. The present study aims to explain the position of the Islamic economics and finance in the GVC. This study employs a qualitative-descriptive method with systematic literature review approach. By collecting secondary data using strict-processing stages and content analysis techniques, the author manages to meet the study’s purpose. The findings suggest that the Islamic economics and finance have opportunities to boost countries' participation in the GVC activities by harmonizing halal standardization, enhancing financial infrastructures, and providing various financial products. This study contributes to generate government policies and enterprises' decisions in developing the Islamic economics and finance within the GVC framework. It further provides initial insights and potential topics for future studies.